Adiposity throughout the life course and risk of venous thromboembolism. Issue 172 (December 2018) - Hagan, Kaitlin A.; Harrington, Laura B.; Kim, Jihye; Lindström, Sara; Camargo, Carlos A.; Grodstein, Francine; Kabrhel, Christopher
Abstract: Objective: Adult body mass index (BMI) is strongly associated with venous thromboembolism (VTE), however whether earlier-life adiposity or other measures of adult adiposity are associated with VTE risk remains largely unknown. Materials and methods: We evaluated associations of childhood somatotype, BMI in early adulthood, adult adiposity, and change in weight since early adulthood with incident VTE risk over ≥20 years of follow-up among 205, 935 participants from Nurses' Health Studies (NHS/NHS II) and Health Professionals Follow-Up Study (HPFS), ages 29–76 at baseline. We estimated multivariable-adjusted hazard ratios for VTE using Cox proportional hazards models. Results and conclusions: Somatotype in childhood and young adulthood BMI were not significantly associated with VTE risk, after accounting for adult BMI. Adult BMI was strongly associated with VTE in all three cohorts (e.g., multivariable-adjusted HRs comparing ≥35 kg/m 2 vs. <22.5 kg/m 2 : NHS:3.03[95% CI: 2.58, 3.56], NHS II:3.82[95% CI: 3.24, 4.51], HPFS:2.81 [95% CI: 2.08, 3.80]; all p-trends < 0.01). Adult waist circumference was associated with greater VTE risk, even after adjusting for adult BMI (all p-trends < 0.01). Increasing weight gain from young adulthood was significantly associated with VTE after adjusting for current BMI among women (HR comparing gain ≥20 kg vs. no change: NHS:1.36[95% CI: 1.13, 1.65], NHS II:1.48[95% CI: 1.17, 1.87]) and not men (HPFS:1.20[95% CI: 0.97, 1.50]). These results indicate that BMI and adiposity are likely more important acutely than cumulatively over time in the etiology and prevention of VTE. Clinically, encouraging weight loss in individuals who are overweight or obese could help reduce VTE risk. Highlights: We confirmed a strong, positive association between adult BMI and risk of VTE. Childhood and young adult adiposity were not significantly associated with VTE. Increasing weight gain from young adulthood was significantly associated with VTE. Adiposity is more important acutely in the etiology and prevention of VTE.